2013
DOI: 10.1111/jvim.12141
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Spironolactone in Dogs with Chronic Heart Failure because of Degenerative Valvular Disease: A Population‐Based, Longitudinal Study

Abstract: Background: Spironolactone treatment in humans is associated with an increased risk of hyperkalemia and renal dysfunction.Hypothesis: Dogs with cardiac disease treated with spironolactone, in addition to conventional therapy, are not at higher risk for adverse events (AEs) than those receiving solely conventional therapy.Animals: One hundred and ninety-six client-owned dogs with naturally occurring myxomatous mitral valve disease. Methods: Prospective, double-blinded field study with dogs randomized to receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 29 publications
(41 reference statements)
4
14
1
Order By: Relevance
“…There was a tendency for serum potassium concentrations to be higher in dogs treated with spironolactone at baseline and the 2 week time point. Nevertheless, all measurements remained within the range of normal values and so this is not a source of pharmacovigilance concern nor has it been noted as a clinically significant adverse event in the published clinical trials involving spironolactone in dogs [25].…”
Section: Discussionmentioning
confidence: 81%
“…There was a tendency for serum potassium concentrations to be higher in dogs treated with spironolactone at baseline and the 2 week time point. Nevertheless, all measurements remained within the range of normal values and so this is not a source of pharmacovigilance concern nor has it been noted as a clinically significant adverse event in the published clinical trials involving spironolactone in dogs [25].…”
Section: Discussionmentioning
confidence: 81%
“…A safety analysis of dogs involved in the study of Bernay and colleagues showed that those receiving spironolactone, in addition to standard treatment (including an ACEI), were not at higher risk for adverse events (such as death from renal disease and abnormalities in serum sodium, potassium, urea nitrogen, and creatinine), when compared with dogs receiving placebo and standard treatment . In fact, mortality caused by cardiac disease, kidney disease, or both was lower in the group treated with spironolactone.…”
Section: Suppression Of Raasmentioning
confidence: 99%
“…Benefits of ACE inhibitors, pimobendan, and spironolactone in DMVD dogs with CHF have been demonstrated. In all these prospective randomized controlled clinical trials, furosemide was authorized and prescribed in most (66%) to all recruited dogs .…”
Section: Discussionmentioning
confidence: 99%